Selection for remedial intervention: The validation - Dockrat, Shafeeka (My University, 2007)
The Academic Proficiency Assessment battery evaluates language and study skills. This study focused on the internal consistency reliability and predictive validity of this battery for Information Technology students. In terms of reliability, the Time management, Note-taking skills, and Debilitating stress scale on the achievement anxiety questionnaire were found to be internally consistent. However, the items in the English proficiency, Reading comprehension, Memorisation skills, concentration skills and motivating stress scale on the achievement anxiety questionnaire require modification or replacement. Intercorrelations across questionnaires necessitate further streamlining. In terms of predictive validity, a significant negative relationship was found between Note-taking Skills and academic performance (R2 adj = 8,3%). Matric results remain the best predictor accounting for 11% of the variance in CGPA. Cumulatively, Matric results and Note-taking skills accounted for 13,34% of the variance. None of the biographical variables significantly predicted CGPA. Despite the apparent lack of relationship between individual predictors and the criterion, a discriminant function analysis indicated that all the academic proficiencies, with the exception of English proficiency, correctly predicted pass or failure in 72% of the cases. The lack of relationship between English proficiency and pass/failure can be accounted for in terms of the type of courses studied as part of an Information Technology programme.Overall, the results would suggest that Matric results remain the best predictor of academic performance in Information Technology courses, but at a very low level. Given the lack of reliability in the majority of the subtests of the Academic Proficiency Battery, the use of the APA battery for selection for remedial intervention for Information Technology students is not yet justified.
Student Number: 9109265Y A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Arts (Psychology)
Keywords: APA Academic Proficiency Assessment; language and study skills; English proficiency; Reading comprehension; Memorisation skills; Note-taking skills; Academic achievement; Academic Proficiency Battery; Remedial intervention